Construction and functional verification of size-reduced plasmids based on TMP resistance gene dfrB10 - Li, Chun-cao; Hu, Rui; Hua, Xiu-min; Ni, Yi-xuan; Ge, Lu; Zhang, Lu; Yu, Wen; Hao, Ni-xin; Xia, Hui; Fang, Qiang; Tao, Zhi-yong (Microbiology spectrum, 2023)
Antibiotic resistance screening is crucial in the construction of recombinant plasmids. The dfrB10 gene, a short-size trimethoprim (TMP)-resistance type B dihydrofolate reductase gene, is a promising antibiotic drug screening marker for plasmid construction in molecular genetic research. Currently, available plasmid backbones (without the resistance gene) were amplified using PCR, and then we ligated these products with dfrB10 gene fragments via homologous recombination to construct new plasmid vectors with TMP resistance. The cloning, expression, and gene editing functions of the new plasmids based on their different purposes were verified. By successfully replacing the original resistance genes of pUC19, pET28a, pcDNA3.1, and pX330 plasmids with dfrB10 , we constructed a series of plasmids with TMP resistance. The change of the resistance selection marker to TMP did not affect the function of the plasmids compared to the original ones. Furthermore, a short (988 bp) TMP-resistant miniature tool plasmid, pTMi, was constructed based on the pUC19 plasmid. With the use of the dfrB10 gene as a resistance marker under TMP drug screening, various size-reduced tool plasmids can be routinely constructed. These plasmids have similar functions to the original ones and can be used for research applications in molecular genetics. Plasmid size is one of the factors affecting transfection efficacy in most of the molecular genetic research studies. One effective approach for reducing plasmid size is to replace relatively large, conventional antibiotic resistance genes with the short-size dfrB10 gene. The successful construct of a series of dfrB10- based tool plasmids and their functional validation, via comparison with original plasmids, suggest that dfrB10 is a potent drug resistance selection marker. The antibiotic trimethoprim offers convenient usage comparable to that of ampicillin or kanamycin. Additionally, fluorescence analysis has demonstrated the compatibility of TMP with protein expression in various host cells. Based on these findings, TMP- dfrB10 could be an alternative choice for future use in molecular genetic research studies that require miniature plasmids to achieve optimal results.